Investigation of the combined effects of cannabidiol plus naltrexone on alcohol craving in alcohol dependence: study protocol of a phase II randomised, double-blind, placebo-controlled, parallel-group trial : ICONICplus Trial : protocol - Vetter, Sina; Weinberg, Julia; Thomas, Bettina C.; Kirchner, Marietta; Thalmann, Paul; Klose, Christina; Pfisterer, Marlen; Kölsch, Torsten; Oesterle, Selma; Vollstädt-Klein, Sabine; Koopmann, Anne; Lenz, Bernd; et al. (BMJ open, 2025)
Introduction Alcohol dependence (AD) is highly prevalent and has severe consequences on health and quality of life. However, the efficacy of approved pharmacotherapies such as naltrexone (NTX) remains limited, highlighting the need for novel pharmacotherapeutic approaches. Cannabidiol (CBD) is a promising candidate, which has shown potential to reduce craving and alcohol use by modulating brain circuits involved in craving and addiction. Preclinical studies suggest that CBD may enhance NTX’s therapeutic effects. - Methods and analysis This is a three-armed, randomised, double-blind, placebo-controlled parallel group, multicentre phase II clinical trial. A total of 150 patients with AD will be randomised (1:1:1) to receive either 800 mg or 1200 mg CBD plus 50 mg oral NTX or placebo plus 50 mg oral NTX for 14 days. Alcohol craving will be assessed using the Obsessive Compulsive Drinking Scale (OCDS-G) where the primary endpoint is the change from baseline to the end of treatment. Secondary outcomes include craving during the entire study, quality of life, depressive symptoms, anxiety, patient-reported outcomes, neural brain activation, CBD plasma levels, time to relapse, alcohol use and treatment safety. For the comparison of each experimental group to the control group, a strata-adjusted (centre and baseline OCDS-G) van Elteren test is applied with adjustment for multiple testing by Bonferroni-Holm. - Ethics and dissemination The trial has been approved by the Ethics Committee and the competent authority (ID: B_03510). All participants will provide written informed consent. An independent Data and Safety Monitoring Board will monitor safety. This trial complies with national and international regulations. - Trial registration number NCT06845124; EU Trial Number: 2024-518164-12-00.
Gesehen am 06.11.2025